Comparison of Al-Ghazali and Emile Durkheim's Concept of Moral Education: Relevance for Contemporary Global Society - Farham, Mu'taz (Riviera Publishing, 2025)
The purpose of this study is: to find out the concepts of Al-Ghazali and Emile Durkheim about the moral education of modern society and to find out the similarities and differences in the concepts of the two figures about the moral education of modern society. The method used in writing this study is the Paedagogic approach method (Islamic Education). From the results of the data processing, it was concluded that: Al-Ghazali's concept of moral education is individual and religious while Emile Durkheim's concept of moral education is social, rational and secular. The similarity between the concepts of Al-Ghazali and Emile Durkheim is that they both recognize the existence of the highest moral authority as a guiding principle in human life, while the difference between the two lies in the concept and essence of moral education, Al-Ghazali is more individualist and Durkheim is socialist.